Application of Talent Management: Assessment and Psychological Test Functions - Siti Annisa Wahdiniawati; Didin Sjarifudin; Lucy Lidiawati Santioso; Fitria Ariyani; Wenny Desty Febrian (Dinasti Publisher, 2024)
This article aims to present an in-depth analysis of the phenomena, problems, and shortcomings in implementing talent management, especially in the context of assessment and psychological test functions. This effort is aimed at increasing understanding of the complexities and challenges faced by organizations in maximizing optimal utilization of talent. This article uses a quantitative approach, which looks for the relationship between existing variables from problems between independent and dependent variables. The population of this study is several leaders in various Umrah and Hajj Travel companies in Depok and Bekasi, with maximum questionnaire distribution and collected answers that returned as many as 35 respondents. Then this data will be processed. Data analysis after getting questionnaire answers returned with data analysis techniques using SPSS 24, by looking for influences between independent and dependent variables. From the analysis conducted, it can be concluded that both Assessment and Psychological tests have a significant influence on Talent Management. This shows the importance of using holistic assessment methods in managing talent within an organization. Careful assessment of employees not only helps in identifying existing talent but also allows organizations to develop more effective talent management strategies. It is recommended from the results of this article that organizations be advised to involve different types of assessments, including assessments and psychological tests, in their talent management processes. Thus, they can gain a more holistic understanding of employees and maximize the potential of existing talent.